Implementation of the New Metric Procedure of Multidecisions Makers Choice for Use in Large-zcale Voting Cases - Savadogo, Zoïnabo; Pagbelguem, Rasmané (European Journal of Applied Sciences, 2025)
The problem of aggregating group preferences into a collective or consensual preference has been tackled since the 18th century by Borda and Condorcet. Since then, several authors have proposed aggregation methods based on social choice theory and metric procedures. However, the use of these metric procedures in decision-making processes today is very limited, and this is explained by the fact that their algorithms recommend multiple complex computations if the number of decision-makers (voters) and the number of alternatives (candidates) is high. To facilitate and popularize the use of metric procedures, it is therefore necessary to equip them with tools or computer programs. It is in this context that we propose in this article a python implementation of the New metric procedure of multidecisions makers choice . In this way, we have been able to set up a program that perfectly integrates the NPMCD algorithm. It is proving to be very efficient, as it allows us to obtain results in a very short time.